The Character Education for Cosmological and Ecological Awareness in Pesantren - Nur, Evita; Junaedi, Mahfud (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper aims to formulate a model of character education in shaping students' awareness about the balance of cosmology and ecological continuity based on its implementation at As-Suffah Institute Rembang. The research method used is a qualitative case study. The data were obtained from in-depth interviews using snowball sampling, participant observations, and reference studies related to character education, pesantren, cosmological relations, and ecological crisis. The collected data was analyzed through the Miles and Huberman interactive analysis model, consisting of data reduction, data presentation, and data verification. The result of this study is As-Shuffah Institute developed a character education model based on the concept of Islamic Cosmology reflected from Suluk Syahadatain Sheikh Achmad Mutammakin and practical experience of KH. Ubaidillah Achmad in the assistance of the community Tolak Semen Kendeng. Character education steps used include four strategies, namely Uswah hasanah, the study of the yellow book riyaḍah, and Sufistic counseling. Therefore, students can be aware of the central identity in religion, such as how much monotheism and faith can produce the broadest possible benefit for humanity (the gift of the universe).